THE ANALYSIS OF ACCEPTANCE OF HOSPITAL INFORMATION MANAGEMENT SYSTEM (HIMS) USING TECHNOLOGY ACCEPTANCE MODEL METHOD - Setiawati, Erma; Trisnawati, Rina; Diana, Ulfi (Riset Akuntansi dan Keuangan Indonesia, 2019)
The purpose of this study was to determine the acceptance of Hospital Management Information Systems related to accounting transactions using the Technology Acceptance Model (TAM) methode. Constructs in TAM used are Perceived Ease of Use, Perceived Usefulness, Behavior Intention to Use, and Actual Technology Usage. The population in this study were users of systems related to accounting transactions, with a total of 150 people. The sampling technique using the convenience non random sampling method. The data in this study were obtained by distributing questionnaires to 150 respondents. Data analysis using SEM-PLS with WarpPLS 5.0 software. The results showed that Perceived ease of use had an effect on Perceived usefulness and Behavior Intention to Use. Whereas, Perceived Usefulness influences Behavior Intention to Use, and Behavior Intention to Use has an effect on Actual Technology Usage. Keywords: Technology Acceptance Model, Partial Least Square, Hospital Management Information System, Accounting Management System